Can Destigmatizing Mental Health Increase Willingness to Seek Help? Experimental Evidence from Nepal - Lindsey Lacey; Nirajana Mishra; Priya Mukherjee; Nikhilesh Prakash; Nishith Prakash; Diane Quinn; Shwetlena Sabarwal; Deepak Saraswat (CESifo GmbH, 2024)
We conducted a randomized control trial to study the impact of two information messages aimed at reducing the stigma associated with mental illness on the willingness to seek mental healthcare among adults in Nepal. The first intervention shares information about the prevalence of mental health issues and the efficacy of treatment. The second intervention shares information about the mental health struggles of a Nepali celebrity and how he benefited from treatment. We find three results. First, compared to a no-information control group, both interventions increase participants' stated willingness to seek mental health treatment. This effect is driven by participants with high personal and anticipated stigma, less severe symptoms of depression and anxiety, and who hold strong beliefs about conformity to masculinity. Second, the impact on participants' stated willingness to seek mental health treatment mirrors their willingness to pay for counseling. Third, participants are, on average, more likely to report willingness to seek help when the enumerator is female.
Keywords: I12; I15; 330; mental health; stigma; prejudice; seeking help; celebrity; Nepal